1960
DOI: 10.1042/bj0760438
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of potassium ions across a concentration difference by isolated rat-liver mitochondria

Abstract: The reduction of coenzymes by malate and succinate was much less sensitive to dinitrophenol than that by pyruvate; relatively high ratios (2*5-18) of reduced to oxidized coenzyme could be obtained with concentrations of dinitrophenol of 1IOpM and 0.1 mm. 9. The maintenance of reduced coenzyme by endogenous substrate and pyruvate was enhanced for a short time by amytal, the effect usually being maximal after about 30 min. of incubation. Subsequently there was a rapid decline in the amount of reduced coenzyme. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1961
1961
1972
1972

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…12) must represent the consequence of turnover of a labile fraction. In common with Amoore (1960) we find that though some 40% of the K+ is exchanged within 1 min. this proportion does not then increase over 20min.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…12) must represent the consequence of turnover of a labile fraction. In common with Amoore (1960) we find that though some 40% of the K+ is exchanged within 1 min. this proportion does not then increase over 20min.…”
Section: Resultssupporting
confidence: 69%
“…this proportion does not then increase over 20min. Amoore (1960) did obtain further exchange in 40min. and still more in 60min., but at these times there had been appreciable losses of K+.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of penetration of respiration-inhibited or uncoupled mitochondria by alkali-metal cations The results just described are difficult to reconcile with the generally accepted view that K+ hardly penetrates the mitochondrial membrane at all in the absence of ionophorous antibiotics (see, e.g., Gamble, 1957; Amoore & Bartley, 1958;Amoore, 1960;Rottenberg & Solomon, 1965;Christie et al, 1965;Harris et al, 1967) or enters in sluggish antiport for H+ (Mitchell & Moyle, 1967, 1969. Repetition of the swelling experiments described by Chappell & Crofts (1966) as a criterion of mitochondrial permeability revealed that respiration-inhibited blowfly flightmuscle mitochondria do not swell in iso-osmotic potassium chloride, potassium acetate or tetramethylammonium acetate solutions, whereas they swell with great rapidity in iso-osmotic ammonium acetate or phosphate solutions, supporting the idea that the K+ ion is indeed a non-penetrant when mitochondria are not respiring.…”
Section: Conditionmentioning
confidence: 87%
“…For some time there has been general consensus that the inner mitochondrial membrane is essentially impermeable to alkali-metal cations. This view, originally suggested by the observation that a portion of the mitochondrial K+ is retained during sucrose washing (Spector, 1953;Bartley & Davis, 1954;Amoore, 1960) and by the osmotic behaviour of mitochondria in solutions of potassium salts (Chappell, 1954;Tedeschi, 1961), was strengthened by the demonstration of a low rate of exchange of endogenous K+ with added 42K (Gamble, 1957;Amoore & Bartley, 1958). Such exchange experiments removed the ambiguity of earlier work in which gross fluxes of K+ were involved, in that the latter are always associated with the movement of at least one other ion, which may be the limiting factor.…”
mentioning
confidence: 99%